Primary splenic diffuse large B-cell lymphoma presenting with a gastrosplenic fistula: Case report - Hurerah Nawaz; Josh Greaser; Irfan Amir Kazi; Ayesha Nasrullah (Radiology Case Reports)
Primary splenic diffuse large B-cell lymphoma (PS-DLBCL) is a rare manifestation of malignant lymphoma. Although DLBCL is the most common subtype of non-Hodgkin lymphoma, primary splenic involvement is uncommon. Additionally, a gastrosplenic fistula at initial presentation is even more rare and poses a diagnostic challenge for the radiologist. The clinical and imaging picture can be identical to a splenic abscess with a secondary gastrosplenic fistula formation (GSF), leading to a diagnostic conundrum. Hence, radiologists need to be familiar with this entity for correct diagnosis and appropriate clinical management.